Solar moss patterns: Heating of coronal loops by turbulence and magnetic connection to the footpoints - R. Kittinaradorn (2018)
We address the origin of the patchy dark and bright emission structure, known as "moss," observed by TRACE extreme ultraviolet observations of the solar disk. Here we propose an explanation based on turbulent, patchy heat conduction from the corona into the transition region. Computer simulations demonstrate that magnetic turbulence in coronal loops develops a flux rope structure with current sheets near the flux rope boundaries. Localized heating due to current sheet activity such as magnetic reconnection is followed by heat conduction along turbulent magnetic field lines. The field line trajectories tend to remain near the flux rope boundaries, resulting in selective heating of the plasma in the transition region. This can explain the network of bright regions in the observed moss morphology. © 2009. The American Astronomical Society.